Internal dynamics of a sustainable city: the case of Nilai Municipality Council - Shaharuddin Idrus,; Abdul Samad Hadi,; Abdul Hadi Harman Shah,; Ahmad Fariz Mohamed, (Environmental Management Society, Malaysia, 2007)
This paper is based on the premise that spatial relationships and space-time activities contribute to the liveability of city. The first part of this paper discusses the sustainable city concept using the idea of liveability. The paper then presents the scenario of the Nilai Municipality to elucidate on what makes for the vibrancy of a city. The paper concludes with some thoughts on sustainable urban living in an intermediate city